2019
DOI: 10.1002/jcb.28663
|View full text |Cite
|
Sign up to set email alerts
|

Effects of quercetin on microRNAs: A mechanistic review

Abstract: MicroRNA (miRNA)-dependent pathways are one of the newest gene regulation mechanisms in various diseases, particularly in cancers. miRNAs are endogenous noncoding RNAs with about 18 to 25 nucleotide length, which can regulate the expression of at least 60% of human total genome posttranscriptionally. Quercetin is the most abundant flavonoid in a variety of fruits, flowers, and medical herbs, known as a strong free radical scavenger that could show antioxidant, anti-inflammatory, and antitumor activities. Recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 148 publications
0
20
0
Order By: Relevance
“…Currently QS is marketed as a dietary supplement in several countries [15]. The protective effect of QS against cancer is due to its effect on miRNAs and their targets [16,17]. Sonoki et al showed that in lung adenocarcinoma cell lines, QS decreases claudin-2 expression through up-regulation of miRNA-16, which leads to reduction in proliferation and migration in lung cancer [18].…”
Section: Introductionmentioning
confidence: 99%
“…Currently QS is marketed as a dietary supplement in several countries [15]. The protective effect of QS against cancer is due to its effect on miRNAs and their targets [16,17]. Sonoki et al showed that in lung adenocarcinoma cell lines, QS decreases claudin-2 expression through up-regulation of miRNA-16, which leads to reduction in proliferation and migration in lung cancer [18].…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin, β‐sitosterol and kaempferol are common compounds found in many herbal medicines. Many scientific reports recognized that they possess antinociceptive, anxiolytic and sedative effects, analgesic, immunomodulatory, antimicrobial, anticancer, anti‐inflammatory, protective effects on respiratory diseases, wound‐healing effects, antioxidants, and so on [26–31] . Because of their numerous biological functions, they are considered as biologically active compounds and have been studied for the treatment of diseases through network pharmacology methods.…”
Section: Discussionmentioning
confidence: 99%
“…This result may be mediated by the increased expression of Ucp-1 in sWAT [118]. Although the role of miRNAs as a potential mechanism involved in the regulation of the browning process has not been specially described, some miRNAs could be implicated in the inflammatory response [119]. In a recent study, the effect of quercetin on miR-155 expression in RAW264.7 macrophages stimulated with lipopolysaccharide (LPS) was evaluated.…”
Section: Food Compounds Related To the Browning Processmentioning
confidence: 99%